ASSESSMENT OF AFLATOXIN B1 IN COMMERCIAL POULTRY FEED AND FEED INGREDIENTS - M. A. Anjum; S. H. Khan; A. W. Sahota; R. Sardar (Journal of Animal and Plant Sciences, 2012)
A total of 487samples (77 and 410 of poultry feed ingredients and poultry feed, respectively) received from various parts of the country were analysed for detection of Aflatoxin B1 (AFB1). Overall incidence of AFB1 in feed ingredients was 60 percent. The average contamination and maximum levels of AFB1 were 37.62 and 56 g/kg, respectively, whereas, the incidence in poultry feed samples was 44.39 percent with average contamination and maximum levels of 23.75 and 78 g/kg, respectively. However, maximum level of AFB1 was higher (78g/kg) in poultry feed samples as compared to feed ingredients (56g/kg). Furthermore, higher incidence and average contamination level of AFB1 were recorded in mash feeds (49.68 percent and 25.12g/kg, respectively) than in crumb feeds (41.32 percent and 22.37g/kg, respectively). A higher incidence of AFB1 was observed during the rainy months i.e. July & August in 2009 (53.85 &60.86 percent, with contamination levels of 56 & 56 g/kg, respectively) and in 2010 (68.18 & 69.44 percent with contamination levels of 78 & 56 g/kg, respectively) than in other months of these years.
Keywords: Aflatoxin B1; incidence; poultry feed ingredients; poultry feed.